Hubungan Antara Durasi Dan Frekuensi Penyemprotan Pestisida Dengan Keluhan Iritasi Kulit Pada Petani Di Desa Raanan Baru Kecamatan Motoling Barat - Adeleide Michelle Rumengan; Vennetia Ryckerens Danes; Oksfriani Jufri Sumampouw; Odi Pinontoan; Sri Seprianto Maddusa (VitaMedica : Jurnal Rumpun Kesehatan Umum, 2026)
Skin irritation is one of the most common health problems experienced by farmers due to pesticide exposure during spraying activities. This study aimed to analyze the relationship between the duration and frequency of pesticide spraying and skin irritation complaints among farmers in Raanan Baru Village, West Motoling District. This quantitative analytical study employed a cross-sectional design and was conducted from March to April 2026. A total of 55 respondents were selected from 286 active pesticide-using farmers using a purposive sampling technique. Data were collected through structured questionnaire-based interviews and analyzed using the Spearman's rank correlation test with a significance level of p < 0.05. The results showed that the average spraying duration was 2.35 hours per day, while the average spraying frequency was 2.38 times per week. There was a significant positive correlation between spraying duration and skin irritation complaints (r = 0.315; p = 0.019) and between spraying frequency and skin irritation complaints (r = 0.346; p = 0.010), with both correlations classified as weak. The findings indicate that longer spraying duration and higher spraying frequency are associated with increased skin irritation complaints among farmers.